Penganggaran Berbasis Kinerja sebagai Upaya Meningkatkan Akuntabilitas Keuangan: Studi Literatur - Chindy Manika Sari; Fillah Ardhi Fadhillah; Tries Ellia Sandari (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the role of performance-based budgeting in enhancing financial accountability in the public sector through a literature review approach. Performance-based budgeting is understood as a budgeting system that emphasizes the linkage between planning, budget allocation, and measurable performance outcomes. The research method employed is a literature study that reviews textbooks, national and international scientific journals, and academic publications relevant to performance-based budgeting and financial accountability. The findings indicate that performance-based budgeting contributes positively to the improvement of financial accountability through greater transparency in budget utilization, the strengthening of reporting systems, and the enhancement of managerial decision-making quality. The literature also reveals that the successful implementation of performance-based budgeting is strongly influenced by the clarity of performance indicators, participation in the budgeting process, and the effectiveness of management control systems. The findings of this study are expected to serve as a conceptual reference for governments and researchers in developing budgeting practices that are more accountable and performance-oriented.